'Give It Up!': A Macro-Social Marketing Approach to India's Clean Cooking Fuel Access. (September 2022) - Jagadale, Sujit Raghunathrao; Kemper, Joya
This paper examines how the Government of India (GOI) used macrosocial marketing (MSM) to address the issues of clean cooking fuel accessibility and affordability and structural inequalities in subsidy redistribution. It highlights a novel MSM application to address chrematistics in marketing systems. Two initiatives established by the GOI are examined. "Give It Up" encourages wealthier households to surrender liquid petroleum gas (LPG) subsidies, leaving these to poorer families, and Pradhan Mantri Ujjwala Yojana (PMUY) installs LPG connections for poor, rural women. The research explores how the GOI has addressed economic inefficiencies and structural inequalities, focusing on institutional norms and affordability, accessibility, awareness, and acceptability (the "4As"). The research expands the theoretical boundaries of MSM in relation to poverty and identifies its capacity to affect individual and systemic change through formal and informal institutional changes. Although new institutional norms were adopted, PMUY could not address the ongoing affordability of LPG, despite the changes to LPG subsidies.